Condensation heat transfer in square, triangular, and semi-circular mini-channels - Derby, Melanie M.; Lee, Hee Joon; Peles, Yoav; Jensen, Michael K. (My University, 2012)
Condensation heat transfer coefﬁcients in mini-channels were measured with smaller measurement uncertainties than previously obtained using three specially designed copper test sections. Single-phase experiments validated the approach. Data are reported for R134a in 1 mm square, triangular, and semicircular multiple parallel minichannels cooled on three sides. A parametric study was conducted over a range of conditions for mass ﬂux, average quality, saturation pressure, and heat ﬂux. Mass ﬂux and quality were determined to have signiﬁcant effects on the condensation process, even at lower mass ﬂuxes, while saturation pressure, heat ﬂux, and channel shape had no signiﬁcant effects. The lack of shape effects were attributed to the three-sided cooling boundary conditions. Because there was no signiﬁcant surface tension enhancement, the macro-scale Shah (2009) [26] correlation best predicted the data, with a mean average error (MAE) of 20–30% for all geometries.
Citation: Derby, M., Lee, H. J., Peles, Y., & Jensen, M. K. (2012). Condensation heat transfer in square, triangular, and semi-circular mini-channels. International Journal of Heat and Mass Transfer, 55(1–3), 187–197. https://doi.org/10.1016/j.ijheatmasstransfer.2011.09.002
Keywords: Condensation; Heat Transfer; Minichannel; Channel Shape